For a compromised history of education - Por uma história comprometida - Luís Alberto Marques Alves, Portugal (Associação Sul-Rio-Grandense de Pesquisadores em História da Educação (ASPHE), 2015)
Conference closing 10th Luso-Brazilian Congress on the History of Education - Paths and Challenges in the Luso-Brazilian History of Education, Curitiba - 28 august 2014.